Curing and swelling kinetics of new magnetorheological elastomer based on natural rubber/waste natural rubber gloves composites. (November 2019) - Hayeemasae, Nabil; Ismail, Hanafi
This article proposes a new type of magnetorheological elastomer (MRE) based on natural rubber (NR) and waste natural rubber gloves (wNRg) blends. The material properties of the MRE samples were investigated with specific focus on the curing and swelling kinetics. Two different series were prepared; the first used carbonyl iron (CI) as the single filler in the MRE, whereas the second hybridized CI with carbon black (CB) to prepare an MRE resistant to solvents. The results show that most properties depend strongly on the nature of both fillers. The higher thermal conductivity of the CI caused a substantial decrease in both the scorch and curing times and the activation energy in the curing process. Based on the diffusion study, a higher volume of fillers in the rubber composites resulted in a greater area of blockage and restricted the penetration of the solvent tested throughout the composites, irrespective of whether CI alone or in combination with CB was used in the composites.